(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of a health education intervention on improving knowledge and self-administration practices of subcutaneous insulin injection among diabetic inpatients at Bach Mai Hospital. Methods: A quasi-experimental study was conducted from January to July 2025 among 94 patients with diabetes mellitus who were prescribed subcutaneous insulin therapy. Patients’ knowledge and insulin injection practices were assessed before and after the intervention using standardized assessment tools. The intervention consisted of individualized health education using models, leaflets, and instructional videos Results: After the intervention, the mean knowledge score significantly increased from 11,27 ± 2,60 to 17,97 ± 3,03 (p < 0,001). The mean practice scores also improved significantly in both the insulin pen group (12,61 ± 3,19 to 18,64 ± 1,57; p < 0,001) and the syringe group (11,77 ± 2,48 to 17,07 ± 2,81; p < 0,001). Factors significantly associated with knowledge and practice outcomes included education level, residential area, duration of insulin use, recent training on injection (p < 0,05). Conclusion: Health education plays a pivotal role in enhancing patients’ knowledge and skills in insulin self-injection. Strengthening educational interventions is recommended to improve self-care effectiveness among patients with diabetes.